Bahasa Inggris - Risa Fita Hapsari; Tb. Abin Syamsudin; E. Mulyasa; Waska Warta (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
The general objective is to obtain a description of guidance and counseling management services to foster students' character in vocational high school. This research uses a qualitative approach with a case study method. Data collected by interview, observation and documentation are then analyzed with data reduction, data presentation and concluding. The results showed that planning guidance and counseling services by five steps in formulating objectives, arranging the program, setting a time, inventory personnel, inventory of facilities, and infrastructure. Organizing the guidance and counseling services is done with the four steps: assigning personnel, creating an organizational structure, arranging main tasks and functions, and coordinating the program. The five steps of implementing guidance and counseling services are implementing the program, actualizing guidance and counseling principles, following up, utilizing facilities and infrastructure, and cooperating between parties. Supervision of guidance and counseling services is carried out through three steps: supervision, summing up the results of supervision and following up on the supervision results.